Vice and virtue in civil service and research: A methodological critique of the Bo Smith Committee’s studies of civil service compliance with rules and norms - Koch, Pernille Boye; Bischoff, Carina Saxlund (Politica, 2018)
The Bo Smith Committee’s conclusions concerning the state of Danish civil service have had a significant impact on the public debate. The conclusions dismiss the notion that there are any systemic flaws in the interaction between politicians and civil servants, and emphasize extensive compliance with the classic civil service norms. We critically examine the studies on which these conclusions rest and uncover violations of key methodological principles that call into question the validity of the committees conclusions. In fact, the data gives rise to contrary conclusions with respect to compliance with the legality norm. They reveal that a remarkably high number of civil servants are willing to assist in illegal acts. In conclusion, we emphasize the need for more – and better – studies to obtain relevant insights into compliance with key norms in the national civil service.